Enhanced fluorescence of functionalized silica microsphere based on whispering gallery mode for nitrate ester explosives and hexogen vapour detection. Issue 8 (9th February 2017) - Zhang, Xiangtao; Zhu, Defeng; Fu, Yanyan; He, Qingguo; Cao, Huimin; Li, Wei; Cheng, Jiangong
Abstract : A fluorescent sensing platform using a WGM microcavity for nitrate ester explosives and hexogen vapour detection by contact-free method is reported. Abstract : Inspired by the wide application of whispering gallery mode (WGM) resonance in the field of photonics, a robust sensing platform made of a hollow-shell silica microsphere was proposed and employed for the detection of low vapour pressure explosives such as nitrate ester and hexogen (RDX). The fluorescent sensory materials were synthesized by the organo-functionalization of intact hollow silica microspheres with two rationally designed pyrene derivatives as sensing units. The sensing films of fluorescent microspheres (NPC-Py-SiO2 and TPA-Py-SiO2 ) made by solid phase transfer method displayed 92% quenching efficiency towards ethylene glycol dinitrate (EGDN) and an 80% sensing response to nitroglycerin (NG) within 300 seconds. In addition, the quenching efficiency and fluorescent intensity of the dye-functionalized microspheres were greatly enhanced by over 900% and 300% compared with their corresponding fluorophores (NPC-Py and TPA-Py), along with superior stability for practical use. Furthermore, the amplified fluorescent intensity and sensitivity were in accordance with theoretical simulation, which proved the WGM resonance of closely stacked silica microspheres. This study enlarged the application of resonant cavities based on size-controlled and functionalized microspheres by a facile preparation method, providing an agile sensing platform for trace explosives and other chemical species with excellent performance.